Adsorption of Thymol onto Natural Clays of Morocco: Kinetic and Isotherm Studies. (10th February 2020) - Ziyat, Hamid; Naciri Bennani, Mohammed; Hajjaj, Hassan; Qabaqous, Omar; Arhzaf, Said; Mekdad, Soumiya; Allaoui, Safae
Abstract : The present work aims to study the affinity of a component of the thyme essential oil "thymol" to natural Moroccan clay "Rhassoul" using the adsorption technique. The physicochemical characterizations of the purified and modified clay were carried out by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), DTA/TGA, and SEM-EDX. Thymol adsorption tests on the purified Rhassoul (Rh-P) and the modified one by CTAB (Rh-CTAB) were followed by UV-visible spectroscopy. They show that the adsorption isotherms can be described by the Freundlich model and that the kinetics of adsorption is in accordance with the pseudo-second-order model for the two clays. Adsorption capacities obtained were of the order of 6 mg/g for the purified Rhassoul and 16 mg/g for the modified Rhassoul by cetyltrimethylammonium bromide (CTAB). These values show that the modified Rhassoul has a better adsorption capacity compared to the purified Rhassoul.